PySulfSat: An open-source Python3 Tool for modeling sulfide and sulfate saturation - Penny Wieser; Matthew Gleeson (Volcanica, 2023)
We present PySulfSat, an open-source Python3 tool for modeling sulfide and anhydrite saturation in magmas. PySulfSat supports a variety of data types (spreadsheets, Petrolog3 outputs, MELTS tbl files). PySulfSat can be used with alphaMELTS for Python infrastructure to track sulfur solubility during fractional crystallization within a single Jupyter Notebook. PySulfSat allows far more customization of calculations than existing tools. For example, the SCSS2− could be calculated with one model using the sulfide composition from a parameterization released with a different SCSS2− model. There are also functions for calculating the proportion of S6+/STot, allowing modeled SCSS and SCAS values to be converted into total S solubility to compare to natural data. We also contain functions for modeling mantle melting in the presence of sulfides using a variety of SCSS and KD models. Extensive documentation and worked examples are available at ReadTheDocs (https://bit.ly/PySulfSatRTD) along with narrated YouTube videos (https://bit.ly/PySulfSatYouTube).